Mate Crime Victimisation Against People with Disabilities: An Exploratory Study in Sarawak, Malaysia - Tharshini, N. K.; Faizah, Haji Masud; Dolly Paul, Carlo (UPM Press, 2022)
Individuals with disabilities are highly exposed to mate crime victimisation than their non-disabled counterparts. This research aims to identify mate crime victimisation among people with disabilities in Sarawak, Malaysia. Data was quantitatively collected among 151 respondents from various governmental and non-governmental organisations in Kuching, Kota Samarahan, and Asajaya that provide residential care, medical attention, training, work opportunities, basic education, and rehabilitation for individuals with disabilities. It was found that most respondents (females between 18 and 28 years old) experienced mate crime victimisation, particularly financial abuse (F₂‚₁₄₈ = 5.905, p = .003) and sexual abuse (F₂‚₁₄₈ = 10.234, p = .001). It is deemed important to identify mate crime victimisation against such individuals with sufficient proof to enable law enforcement agencies and policymakers to develop optimal approaches and programmes that complement the needs of individuals with disabilities and alleviate potential mate crime victimisations.